2017
DOI: 10.3389/fneur.2017.00309
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence, Prognosis, Early Stroke Risk, and Stroke-Related Prognostic Factors of Definite or Probable Transient Ischemic Attacks in China, 2013

Abstract: The epidemiological characteristics of transient ischemic attacks (TIAs) in China are unclear. In 2013, we conducted a nationally representative, door-to-door epidemiological survey on TIA in China using a complex, multistage, probability sampling design. Results showed that the weighted prevalence of TIA in China was 103.3 [95% confidence interval (CI): 83.9–127.2] per 100,000 in the population, 92.4 (75.0–113.8) per 100,000 among men, and 114.7 (87.2–151.0) per 100,000 among women. The weighted incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…A community-based stroke registry in three cities in China showed that only 16.9% of patients with stroke were aware that their initial symptom represented a stroke 4. In fact, over half of TIA patients with stroke have already developed a stroke within 2 days of symptom onset 1 21. This implies that TIA care should be focussed on pre-TIA care as well as inpatient and outpatient care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A community-based stroke registry in three cities in China showed that only 16.9% of patients with stroke were aware that their initial symptom represented a stroke 4. In fact, over half of TIA patients with stroke have already developed a stroke within 2 days of symptom onset 1 21. This implies that TIA care should be focussed on pre-TIA care as well as inpatient and outpatient care.…”
Section: Discussionmentioning
confidence: 99%
“…A nationally representative cross-sectional survey on strokes and TIAs was conducted in 157 disease surveillance points (DSPs) or survey sites of the 31 provincial regions in mainland China from 1 September 2013 to 31 December 2013 which was described in detail in previous studies 1 5. Briefly, participants with suspected stroke or TIA symptoms were screened from the sampled populations by China’s Centers for Disease Control and Prevention (CDC) investigators and further interviewed by neurologists in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Transient ischemic attack is a warning sign of ischemic stroke. A nationwide multicenter study in China found that 12.3% of patients with transient cerebral ischemia progressed to stroke within 90 days 44 . A systematic review that included 13 RCTs 45 showed that the addition of Chinese herbal medicine to a conventional secondary prevention strategy reduced the stroke event rate in 6 months following a transient ischemic attack (RR = 0.13, 95% CI 0.0‐0.97, n = 148) and at 12 months (RR = 0.42, 95% CI 0.23‐0.75, n = 446).…”
Section: Recommendationsmentioning
confidence: 99%